A critical reflection on the student evaluation of the effectiveness of university teachers in New Zealand - Anthony Harland (Universitat Politècnica de València, 2021)
In this article I write about my experiences of the student evaluation of teaching by drawing on several decades of work as a researcher, teacher and academic developer. I address three complex questions that have received little attention in the literature. These are concerned with the drivers for evaluation, its effectiveness and why it has become embedded in academic practice. Contemporary evaluation practices are theorised as neoliberal and for compliance purposes. I conclude that compulsory evaluations fail in their neoliberal intent and can also be detrimental to teaching and student learning.